Toll-Like Receptors in Esophageal Cancer - Kauppila, Joonas H.; Selander, Katri S. (Frontiers in Immunology, 2014)
Esophageal squamous cell carcinoma and esophageal adenocarcinoma are cancers of high mortality. Esophageal adenocarcinoma develops through Barrett’s esophagus and columnar dysplasia, preceded by gastroesophageal reflux disease. The risk of esophageal squamous cell carcinoma is increased by smoking and alcohol consumption. New treatment options for esophageal cancer are desperately needed. Toll-like receptors (TLRs) play a central role in mammalian immunity and cancer. TLRs are activated by microbial components, such as lipopolysaccharide, flagellin, DNA and RNA, as well as endogenous ligands, including heat-shock proteins and endogenous DNA. This review summarizes the studies on Toll-like receptors in esophageal squamous cell carcinoma and esophageal adenocarcinoma. It has been shown that TLRs 1-10 are expressed in the normal esophagus. In esophageal squamous cell carcinoma, TLRs 3, -4, -7, and 9 have been studied, showing associations to aggressive disease properties. In Barrett’s esophagus and esophageal adenocarcinoma, only TLRs 4, -5 and -9 have been studied. In the review, we discuss the implications of TLRs in esophageal cancer.